2021
DOI: 10.1002/pon.5685
|View full text |Cite
|
Sign up to set email alerts
|

Emotional problem‐related distress screening and its prevalence by cancer type: Assessment by patients' characteristics and level of assistance requested

Abstract: Objective Emotional problem‐related distress is a common issue faced by patients with cancer. However, patients suffering with this emotional burden do not typically seek assistance. This study sought to determine the prevalence of emotional problem‐related distress by cancer type, and identify factors correlated with the level of assistance requested. Methods Using the SupportScreen®, patients were screened for emotional problem‐related distress at their first or second visit to an NCI designated Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, studies of psychological distress in survivors with pelvic LRTIs are very limited. Bergerot et al [ 19 ] showed that patients with gynaecological and gastrointestinal cancers are in general at higher risk of psychological distress. Adams et al [ 2 ] found that more severe pelvic LRTI symptoms across cancer types were associated with higher rates of depression but not with higher rates of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of psychological distress in survivors with pelvic LRTIs are very limited. Bergerot et al [ 19 ] showed that patients with gynaecological and gastrointestinal cancers are in general at higher risk of psychological distress. Adams et al [ 2 ] found that more severe pelvic LRTI symptoms across cancer types were associated with higher rates of depression but not with higher rates of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…However, the level of emotional distress is individual. Patients diagnosed with lung, gynecological, breast and gastrointestinal cancer more often suffered with emotional problem-related distress in comparison with prostate and hematological cancer patients [ 23 ]. The level of emotional distress is the highest in the case of lung cancer patients and it was shown by 43% of patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of emotional distress is the highest in the case of lung cancer patients and it was shown by 43% of patients [ 24 ]. Younger age and lower incomes are associated with greater emotional distress faced by patients [ 3 , 23 ]. Morrison et al [ 3 ] reported that women, the employed, current smokers and patients in more advanced lung cancer stages experienced emotional problems at a significantly higher rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research shows that lung cancer surgery is associated with physical and psychosocial challenges; lung cancer patients have one of the highest levels of emotional distress among all cancer types (Bergerot et al, 2021; Carlson et al, 2019). In lung cancer surgery patients, pain, lack of energy, shortness of breath, drowsiness and worrying increased significantly in the first month after surgery and then decreased over time (Oksholm et al, 2015), indicating that the time around surgery is a particularly difficult period.…”
Section: Introductionmentioning
confidence: 99%